Penegakan Hukum Situasional Dalam Menangangi Tindak Pidana Penyelundupan Narkotika Di Indonesia - Endah Cahyani; Nathalina Naibaho (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The rise of narcotics smuggling crimes is a challenge for the Indonesian nation to deal with crimes that are transnational in nature and are extraordinary crimes. Law enforcement against the eradication of nakotika crimes so far has not been effective and has not caused a deterrent effect for perpetrators even though the death penalty has been formulated as an ultimum remedium in criminal law. This study aims to the extent of the effectiveness of law enforcement against narcotics crimes in Indonesia. The methods used in this study are normative research methods and qualitative data analysis. The result of the study is the need for situational law enforcement efforts in dealing with the criminal act of narcotics smuggling to strengthen every component of law enforcement both from the legal component, law enforcement officials, facilities and facilities, society, and culture.Keywords: Law Enforcement; Smuggling; Narcotic. AbstrakMaraknya tindak pidana penyelundupan narkotika menjadi tantangan bagi bangsa Indonesia untuk menangani kejahatan yang bersifat transnasional dan merupakan kejahatan luar biasa. Penegakan hukum terhadap pemberantasan tindak pidana narkotika selama ini ternyata masih belum efektif dan tidak menimbulkan efek jera bagi para pelaku sekalipun telah dirumuskan pidana mati sebagai ultimum remedium dalam hukum pidana. Penelitian ini bertujuan untuk sejauh mana efektivitas penegakan hukum terhadap tindak pidana narkotika di Indonesia. Metode yang digunakan dalam penelitian ini ialah metode penelitian normatif dan analisis data secara kualitatif. Hasil dari penelitian ialah diperlukannya upaya penegakan hukum situasional dalam menangani tindak pidana penyelundupan narkotika untuk memperkuat setiap komponen penegakan hukum baik dari komponen hukum, aparat penegak hukum, sarana dan fasilitas, masyarakat dan budaya.Kata Kunci: Penegakan Hukum; Penyelundupan; Narkotika.